2020
DOI: 10.3390/ijms21249403
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Nanotechnology to Fight HIV Sexual Transmission: The Trip of G2-S16 Polyanionic Carbosilane Dendrimer to Possible Pre-Clinical Trials

Abstract: Development of new, safe, and effective microbicides to prevent human immunodeficiency virus HIV sexual transmission is needed. Unfortunately, most microbicides proved ineffective to prevent the risk of HIV-infection in clinical trials. We are working with G2-S16 polyanionic carbosilane dendrimer (PCD) as a new possible vaginal topical microbicide, based on its short reaction times, wide availability, high reproducibility, and quantitative yields of reaction. G2-S16 PCD exerts anti-HIV activity at an early sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 124 publications
(178 reference statements)
0
9
0
1
Order By: Relevance
“…The DPV has been tested in several application forms, including vaginal gels, films or intravaginal rings [ 29 , 30 , 31 , 32 , 33 , 34 ]. In spite of reaching phase II clinical trials, DPV has been shown to cause side effects such as inflammation, reddening or swelling of the cervix, urinary tract infection, loss of bladder control, headache, pain during sex, and pelvic pain [ 32 , 35 , 36 ] (Else, Taylor et al, 2011; Baeten, Palanee-Phillips et al, 2016; Nel, van Niekerk et al, 2016) [ 1 , 2 , 3 ]. A vaginal ring containing DPV is being tested in adolescent and young women [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPV has been tested in several application forms, including vaginal gels, films or intravaginal rings [ 29 , 30 , 31 , 32 , 33 , 34 ]. In spite of reaching phase II clinical trials, DPV has been shown to cause side effects such as inflammation, reddening or swelling of the cervix, urinary tract infection, loss of bladder control, headache, pain during sex, and pelvic pain [ 32 , 35 , 36 ] (Else, Taylor et al, 2011; Baeten, Palanee-Phillips et al, 2016; Nel, van Niekerk et al, 2016) [ 1 , 2 , 3 ]. A vaginal ring containing DPV is being tested in adolescent and young women [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs are presently seldom used in clinical care. Unfortunately, when tested as microbicides in clinical trials, many vaginal microbicide formulations based on entry inhibitors failed to cause a protective effect due to their lack of efficacy and their unsuitable formulation, which led to irritability and inflammation [ 1 , 2 , 3 ]. Additionally, as happens with other drugs, entry inhibitors are affected by drug resistance mutations and could be affected by viral tropism (e.g., CCR5 antagonists) and subtype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to treatments, nanotechnology has emerged as a viable therapeutic alternative to develop new drugs and treatments against diverse pathogens. In the case of viral infections, we have previously described the potent efficacy of dendrimers against viruses such as HIV-1 and HSV-2, in vitro as well as in vivo [ 11 – 15 ]. Dendrimers are hyperbranched nanoparticles consisting of a central core and several functional groups in the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, carbosilane dendrimers have shown great efficacy as microbicides, specifically G2-S16 [5]. This second-generation dendrimer with a silica core and 16 sulfonate end groups has demonstrated in previous assays that it is capable of destabilizing the GP120-CD4 complex by blocking HIV-1 entry and cell-to-cell fusion [6][7][8] (reviewed in [9]).…”
Section: Introductionmentioning
confidence: 99%